Efficiency of Advanced Oxidation Processes for Detoxification of Industrial Effluents - Iqbal, Munawar; Ahmad Bhatti, Ijaz; Zia-ur-Rehman, Muhammad; Nawaz Bhatti, Haq; Shahid, Muhammad (Asian Journal of Chemistry, 2014)
The possibility of applying photo-catalytic treatment (UV/H2O2/TiO2) to reduce the cytotoxicity and mutagenicity as well as the microbial load of soap and detergent wastewater has been investigated. Wastewater from three soap and detergent industries were collected from Faisalabad, Gujranwala and Sargodha regions of Pakistan. Bioassays such as allium cepa, haemolytic and brine shrimp were utilized to assess the cytotoxicity, while mutagenicity was evaluated through Ames test. The microbial load; bacterial count and total coliform tests were performed under standardized conditions. Along with toxicity appraisal, the water quality parameter such as BOD, COD, DO, pH, TDS and TSS were also measured before and after application of UV/H2O2/TiO2 treatment. A considerable reduction in cytotoxicity and mutagenicity was achieved with the maximum degradation of pollutants. With the application of advanced oxidation treatment complete removal of cytotoxicity and mutagenicity was obtained and results indicate that the advanced oxidation process can be successfully used for toxicity removal, for the improvement of water quality parameters and hence the treated wastewater could possibly be used for irrigation purposes.